Charge-transfer and impulsive electronic-to-vibrational energy conversion in ferricyanide: ultrafast photoelectron and transient infrared studies - Ojeda, José; Arrell, Christopher A; Longetti, Luca; Chergui, Majed; Helbing, Jan (Physical chemistry chemical physics : PCCP, 2017)
The photophysics of ferricyanide in H O, D O and ethylene glycol was studied upon excitation of ligand-to-metal charge transfer (LMCT) transitions by combining ultrafast photoelectron spectroscopy (PES) of liquids and transient vibrational spectroscopy. Upon 400 nm excitation in water, the PES results show a prompt reduction of the Fe to Fe and a back electron transfer in ∼0.5 ps concomitant with the appearance and decay of a strongly broadened infrared absorption at ∼2065 cm . In ethylene glycol, the same IR absorption band decays in ∼1 ps, implying a strong dependence of the back electron transfer on the solvent. Thereafter, the ground state ferric species is left vibrationally hot with significant excitation of up to two quanta of the CN-stretch modes, which completely decay on a 10 ps time scale. Under 265 nm excitation even higher CN-stretch levels are populated. Finally, from a tiny residual transient IR signal, we deduce that less than 2% of the excited species undergo photoaquation, in line with early flash photolysis experiments. The latter is more significant at 265 nm compared to 400 nm excitation, which suggests photodissociation in this system is an unlikely statistical process related to the large excess of vibrational energy.